Dossier: Médicine et arts visuels : La Part de l'Œil. - Matossian, Chakè (Bruxelles : l'Imprimerie Poot, 1995)
Binet, Jacques-Louis ; Calabrese, Omar ; Carlino, Andrea ; Kofman, Sarah ; Le Breton, David ; Lecercle, François ; Leutrat, Jean-Louis ; Makhitarian, Aram ; Pelicier, Yves ; Pigeaud, Jackie ; Richir, Luc ; Seguin, Louis ; Stafford, Barbara
boek